2018
DOI: 10.1186/s40409-018-0176-5
|View full text |Cite
|
Sign up to set email alerts
|

Kn-Ba: a novel serine protease isolated from Bitis arietans snake venom with fibrinogenolytic and kinin-releasing activities

Abstract: BackgroundBitis arietans is a venomous snake found in sub-Saharan Africa and in parts of Morocco and Saudi Arabia. The envenomation is characterized by local and systemic reactions including pain, blistering, edema and tissue damage, besides hemostatic and cardiovascular disturbances, which can cause death or permanent disabilities in its victims. However, the action mechanisms that provoke these effects remain poorly understood, especially the activities of purified venom components. Therefore, in order to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The question then arises of whether using a larger dose of D. siamensis venom can induce coagulopathies in the rabbit model, which requires further investigation. PLA 2 toxins in D. siamensis venom is believed to play a role as a specific antihypertensive component through its effects on releases of thromboxane A 2 (TXA 2 ) [49], prostacyclin (PGI) [44], autacoids such as histamine [38], kinin [50], and interaction with platelets and leukocytes. However, it has been demonstrated that histamine does not appear to play a role in D. russelii venom-induced vasorelaxation in comparison to the presence of the histamine H1 receptor antagonist [38].…”
Section: Comparative Venomics and Cardiovascular Effectsmentioning
confidence: 99%
“…The question then arises of whether using a larger dose of D. siamensis venom can induce coagulopathies in the rabbit model, which requires further investigation. PLA 2 toxins in D. siamensis venom is believed to play a role as a specific antihypertensive component through its effects on releases of thromboxane A 2 (TXA 2 ) [49], prostacyclin (PGI) [44], autacoids such as histamine [38], kinin [50], and interaction with platelets and leukocytes. However, it has been demonstrated that histamine does not appear to play a role in D. russelii venom-induced vasorelaxation in comparison to the presence of the histamine H1 receptor antagonist [38].…”
Section: Comparative Venomics and Cardiovascular Effectsmentioning
confidence: 99%
“…The experimental models here used, and the results obtained, may be useful to understand the role of inflammation in BaV envenomation, hence potentially improving the victim's treatment, in addition to indicating the possible toxins responsible for these symptoms. In this sense, Kn-Ba, a serine protease with fibrinolytic and kinin-releasing activity, was isolated from the Bitis arietans venom [43] and it is also related to the inflammatory process, including the activation of the inflammasome complex and the release of active IL -1β. For this, new studies are being finalized.…”
Section: Discussionmentioning
confidence: 99%
“…Kn-Ba was purified from BaV as previously described [25]. Purified Kn-Ba was diluted in sterile PBS pH 7.2 and stored at −80 • C.…”
Section: Kn-bamentioning
confidence: 99%
“…Kn-Ba is also recognized by antibodies (Abs) present in the horse-serum anti-Bitis spp. venoms [25].…”
Section: Introductionmentioning
confidence: 99%